Risk factors for hospitalization and death due to COVID-19 among frail community-dwelling elderly people: a retrospective cohort study - Azevedo, Daniela Castelo; Assunção, Fernando César Menezes; Castro, Mônica Silva Monteiro de; Valle, Estevão Alves (São Paulo Medical Journal, 2022)
BACKGROUND: Advanced age, multiple chronic diseases and frailty have been correlated with worse prognosis among coronavirus disease 2019 (COVID-19) inpatients. OBJECTIVE: To investigate potential risk factors for hospitalization and death due to COVID-19 among frail community-dwelling elderly people. DESIGN AND SETTING: Retrospective cohort study of patients followed up at a geriatric outpatient clinic in Belo Horizonte, Minas Gerais, Brazil. METHODS: The associations of demographic characteristics (age and sex) and clinical characteristics (frailty, multimorbidity, number of medications with long-term use, obesity, smoking, diabetes mellitus, pulmonary diseases, cardiovascular diseases, cerebrovascular disease, and chronic kidney disease) with the risk of hospitalization and death due to COVID-19 were explored using a multivariable logistic regression model. RESULTS: 5,295 patients (mean age 78.6 ± 9.4 years; 72.6% females) were included. After adjustments, the number of medications with long-term use was found to increase the odds of hospitalization due to COVID-19 (odds ratio, OR: 1.13; 95% confidence interval, CI: 1.06-1.22). Frailty, multimorbidity and diabetes mellitus also increased the odds of hospitalization (OR: 1.06, 95% CI: 1.02-1.09; OR: 1.17, 95% CI: 1.09-1.26; and OR: 2.27, 95% CI: 1.45-3.54, respectively) and the odds of death due to COVID-19 (OR: 1.07, 95% CI: 1.00-1.14; OR: 1.16, 95% CI: 1.03-1.32; and OR: 2.69, 95% CI: 1.79-6.14, respectively). CONCLUSIONS: Multimorbidity, frailty and diabetes mellitus increased the odds of hospitalization and death due to COVID-19 and the number of medications with long-term use increased the odds of hospitalization due to COVID-19 among frail community-dwelling elderly people.